Impact of Curriculum Reforms on the Teaching and Learning of Basic Science in Niger State Secondary Schools - Nkok, Ekaette Anietie Enang; Nkok, Ubong Monday (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2025)
This study was on curriculum reforms and its impact on teaching and learning of Basic Science in secondary schools in Niger State, Nigeria. A survey research design was employed for the study. The population for the study was all the 181 science teachers from all the Government junior secondary schools in Niger state. simple random sampling technique was used to select Ninety- two science teachers from 10 senior secondary schools in education zone B of the state for the study. Three research questions guided the study. A 30 - item researchermade 4- points scale Questionnaire titled, curriculum reforms and its impact on teaching and learning of Basic science (CRITLBS) was employed for the study. Test retest method was used to determine the reliability of the instrument to be 0.71. The instrument was administered on the respondents in the 10 randomly selected schools in 2024/2025 academic session. Data collected was analyzed using mean and standard deviation. A mean score of 2.5 and above was considered significant. The findings of the study revealed positive impacts of science education curriculum reforms on teaching and learning of Basic science with mean scores of 3.2, 2.9, and 3.4 for positive items. Based on the findings, three recommendations were made. Among which is that, Educational stake holders like managers, government among others should always plan for curriculum reforms at regular intervals and teachers well equipped to handle reforms by updating their knowledge and skills through seminars, workshops and symposiums so as to ensure improved quality of teachings particularly in the field of sciences.